LINGUISTIC PRINCIPLES OF CREATING A TEXTBOOK ON LEXICOLOGY - GRDZELYAN, ROUZAN (Bulletin of Yerevan University H: Russian Philology, 2020)
The article discusses the linguistic principles of creating a textbook on the lexicology of the Russian language: the application of the principles of an active dictionary taking into account the factors of the lexical world and lexical grammar, dynamic description of lexical meaning. The article attempts to apply the modern linguistic methodology and research techniques in the field of educational linguistics.